A New Version of a Broadly Applicable, Cross-lingual Meaning Representation Formalism and Its Significance for Biomedical Sciences - Fomichov, Vladimir A. (Informatica, 2024)
The first purpose of the paper is to attract the attention of the scholars in natural language (NL) processing to a new version of a broadly applicable, cross-lingual meaning representation formalism: a new version of the theory of SK-languages (standard knowledge languages) introduced in early 2000s by the theory of K-representations (knowledge representations), or TKR. A collection of original expressive mechanisms for constructing semantic representations (SRs) of scientific notions’ definitions is suggested, its joint work is demonstrated. A special attention is paid to indicating the advantages of TKR-based approach to building SRs of scientific definitions in comparison with Universal Conceptual Cognitive Annotation, Abstract Meaning Representation, and Uniform Meaning Representation. New precious and broad prospects of describing semantic structure of NL-texts pertaining to biomedical sciences are indicated. The second purpose is to improve an algorithm (introduced in a previous paper of the author) constructing SRs of scientific notions’ definitions and to illustrate its principal ideas. The output SRs are the expressions of SK-languages. The methodological basis is TKR. In particular, the suggested algorithm of scientific definitions’ semantic parsing includes a complex procedure based on the algorithm of semantic parsing SemSynt1 given by TKR. The original features of the suggested algorithm constructing SRs of scientific definitions are shown.